MMP-7 expression is associated with a higher rate of tumor spread through air spaces in resected lung adenocarcinomas. (January 2023) - Yamada, Kaede; Kadota, Kyuichi; Fujimoto, Syusuke; Yoshida, Chihiro; Ibuki, Emi; Ishikawa, Ryo; Haba, Reiji; Yokomise, Hiroyasu; Yajima, Toshiki
Highlights: We analyzed MMP-7 expression in patients with therapy-naive lung adenocarcinoma. MMP-7 expression was correlated with aggressive tumor behavior. MMP-7 expression was associated with a poor prognosis. High MMP-7 expression was an independent predictive factor for STAS. Abstract: Objectives: The spread through air spaces (STAS) of adenocarcinoma (ADC) is a unique pattern for local invasion, which comprises the spread of tumor cells within air spaces beyond the tumor edge without a direct connection with the primary tumor. Matrix metalloproteinase-7 (MMP-7), a secreted proteolytic enzyme that degrades various extracellular matrix components and other substrates, regulates several pathophysiological processes as well as the occurrence and development of cancers in humans. Here, we retrospectively analyzed a cohort of Japanese patients with treatment-naive, surgically-resected lung ADC to assess whether MMP-7 is associated with STAS development and if it could be used as a predictor of STAS. Materials and methods: We performed histological evaluation using hematoxylin and eosin staining and immunohistochemical analysis using microarrays. Thereafter, we scored the examined tissues for immune markers to identify significant tumor STAS predictors. Results: We identified that high MMP-7 expression is an independent predictor of a high STAS incidence. Multivariate analysis revealed that MMP-7 expression was correlated with tumor behavior and poor prognosis. Furthermore, STAS remained significantly associated with a higher risk of ADC recurrence. Conclusion: The development of tumor STAS could be promoted by the functioning of MMP-7. This study could be a crucial basis for future investigations on the detection of tumor STAS.